2009
DOI: 10.1007/s10571-009-9376-4
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Mechanisms Leading to Neuroprotection/Ischemic Tolerance: Effect of Preconditioning on the Stress Reaction of Endoplasmic Reticulum

Abstract: Ischemic tolerance can be developed by prior ischemic non-injurious stimulus preconditioning. The molecular mechanisms underlying ischemic tolerance are not yet fully understood. The purpose of this study is to evaluate the effect of preconditioning/preischemia on ischemic brain injury. We examined the endoplasmic reticulum stress response (unfolded protein response (UPR)) by measuring the mRNA and protein levels of specific genes such as ATF6, GRP78, and XBP1 after 15 min 4-VO ischemia and different times of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
33
0

Year Published

2009
2009
2018
2018

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 50 publications
(34 citation statements)
references
References 38 publications
1
33
0
Order By: Relevance
“…32,58,97 A prolonged mild ischemic stimulus may lead to the cell having a tolerable amount of ER stress, thereby dictating that further insult will not significantly harm the cell by attenuation of the ER stress response after an acute ischemic episode. 98 Interestingly, overexpression of the cardiac sodium/hydrogen exchanger (NHE1) resulted in upregulation of ER stress. 99 It had been previously determined that NHE1 expression is maladaptive during cardiac function but the unexpected increase in the UPR (during NHE1 overexpression), led to enhanced survival of the mouse heart under ischemic conditions.…”
Section: Er Stress: Pathological Versus Physiological?mentioning
confidence: 99%
“…32,58,97 A prolonged mild ischemic stimulus may lead to the cell having a tolerable amount of ER stress, thereby dictating that further insult will not significantly harm the cell by attenuation of the ER stress response after an acute ischemic episode. 98 Interestingly, overexpression of the cardiac sodium/hydrogen exchanger (NHE1) resulted in upregulation of ER stress. 99 It had been previously determined that NHE1 expression is maladaptive during cardiac function but the unexpected increase in the UPR (during NHE1 overexpression), led to enhanced survival of the mouse heart under ischemic conditions.…”
Section: Er Stress: Pathological Versus Physiological?mentioning
confidence: 99%
“…13,14 Several studies have shown that transient cerebral ischemia activates XBP1 mRNA splicing, which protects cell survival from ischemia/reperfusion-induced cell damage and enhances cell apoptosis. [15][16][17][18][19] Our previous study showed that XBP1 expression and splicing responded to local flow pattern and was related to EC proliferation status. 20 In the present study, we demonstrate that XBP1 mRNA splicing is involved in VEGF signaling and contributes to EC proliferation and angiogenesis in ischemic tissues.…”
mentioning
confidence: 99%
“…The number of dead nerve cells in the hippocampus and striatum was markedly decreased in homozygous Chop knockout mice. Lehotský et al (2009) reported that the apoptosis rate and CHOP and caspase-12 expression levels decreased while GRP78 increased at each time point in rats after a 10-min ischemia. In our experiments, GRP78 and CHOP expression levels exhibited a different time course to reach maximum levels in hypertensive rats in response to I/R.…”
Section: Discussionmentioning
confidence: 97%